Green synthesis silver nanoparticles via Eichhornia Crassipes leaves extract and their applications - Leena V. Hublikar (Elsevier, 2021)
Recent times sustained efforts have been made in the bottom-up approach and biological Ag nanoparticles synthesis, in present work synthesized silver nanoparticles via green synthesis from the Eichhornia crassipes (EC) leaf extract AgNPs at room temperature with pH of 10–12. Synthesized AgNPs characterized thoroughly for phase purity and morphology by various characterization techniques. Phytochemical activities of Eichhornia crassipes (EC) leaf extract were shown that main constituents flavonoids, quercetin enhances the conversion of Ag ​+ ​to Ag0. This is also confirmed through the electronic property (EHOMO and ELUMO) of EC leaf extract, which was analyzed through quantum chemical studies. Further the antibacterial activity of AgNPs was screened on E. coli and S. aureus. The result reveals that AgNPs has good antibacterial properties towards the bacteria E. coli. The AgNPs is dedicated also in testing the effectiveness of aluminum corrosion in the acid system at room temperature using Tafel plots, atomic absorption spectroscopy, and AC impedance spectroscopy techniques. Corroded aluminum pieces were observed by using the SEM technique.